Patterned two-dimensional VX2, transverse and vertical VX2 / TMDs heterojunction and preparation and application thereof

Through laser etching and hydrochloric acid treatment, the problem of difficult channel length in two-dimensional VX2 nanosheets and heterostructures is solved, and controllable patterning is realized, which promotes the efficient manufacturing of two-dimensional VX2 materials and their heterostructures is improved. , provides a high-quality material platform for electronic devices.

CN119314869AActive Publication Date: 2025-01-14HUNAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411184045.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-26
Filing Date
2024-08-27
Publication Date
2025-01-14
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and simply prepare patterned two-dimensional VX2 nanosheets with controllable channel lengths and their heterostructures, especially when manufacturing two-dimensional metal nanosheets, the process is complicated and the channel length is difficult to control.

Method used

Using laser etching and hydrochloric acid solution treatment methods, the patterning of two-dimensional VX2 materials is achieved by controlling the laser power intensity and processing time, ensuring the controllability of the channel length, and on this basis, the patterned two-dimensional transverse direction is prepared. or vertical VX2/TMDs heterojunction.

Benefits of technology

The preparation of patterned two-dimensional VX2 materials and heterostructures with clean and lossless and controllable channel length is realized, providing a high selectivity and high crystallinity material platform suitable for the manufacturing of electronic devices, especially vertical VX2/TMDs Patterning of metal/semiconductor heterostructures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314869A_ABST
    Figure CN119314869A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of two-dimensional materials, in particular to a preparation method of a patterned two-dimensional VX2 material, which comprises the following steps: obtaining a two-dimensional VX2 material, then carrying out patterned etching treatment on the two-dimensional VX2 material by using laser, and then treating the two-dimensional VX2 material by using a hydrochloric acid solution to obtain the patterned two-dimensional VX2 material. X is S or Se; and the power intensity of the laser is less than 3.5 * 10 < 5 > W / cm < 2 >. The invention also comprises the material prepared by the preparation method and preparation of the material in transverse and vertical heterojunctions and devices. According to the method, the laser with the power intensity is creatively adopted to etch the two-dimensional VX2 material, and hydrochloric acid treatment is further combined, so that patterning of the two-dimensional VX2 material can be simply realized, the clean and lossless patterned two-dimensional VX2 material with controllable channel length can be prepared, and in addition, the yield of the patterned two-dimensional VX2 material is improved. And the transverse or vertical heterojunction which is high in cleanliness, lossless and excellent in performance can be obtained on the basis of the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of two-dimensional material preparation, and specifically relates to the field of controllable preparation of two-dimensional material patterned heterostructures. Technical Background

[0002] Two-dimensional (2D) semiconductor heterostructures have attracted attention due to their unique physical properties and potential applications in future electronics, catalysis, sensory (sensors), optoelectronics, and energy storage. Two-dimensional materials with different crystal structures can form lateral heterostructures or vertical van der Waals heterostructures, providing a rich platform for exploring the transport of carriers and photons within atomic-scale interfaces. Chemical vapor deposition (CVD) is one of the most commonly used methods to prepare transition metal chalcogenide (TMD) heterostructures. For example, using the designed Au(111) / W-Re alloy foil substrate, a 100% overlapped ReS2 / WS2 vertical heterostructure was synthesized by one-step CVD. Ajayan group 1 A one-step CVD method is reported to selectively prepare lateral or vertical WS2 / MoS2 heterostructures by temperature triggering. The two-step CVD method can also be used to produce various TMD heterostructures such as WSe2 / MoSe2, SnSe2 / MoS2, and WS2 / MoS2.

[0003] In addition to the widely explored semiconductor heterostructures, the preparation of metallic TMD (m-TMD) and semiconductor TMD (s-TMD) heterostructures is also very important because they have great potential in creating high-quality contacts and improving device performance. For example, Shi et al. 2 Using CVD-grown VTe2 nanosheets as contact metals for monolayer MoS2 devices, the resulting field-effect mobility is six times higher than that of conventional Ti / Au electrode contacts. Ji et al. 3 Using CVD-grown VS2 as the contact electrode for the monolayer MoS2, the contact resistance obtained is about 1 / 4 of the Ni / Au metal contact resistance. However, the fabrication of the above heterostructure devices requires the transfer of two-dimensional metal nanosheets, which is a complicated process. In addition, the channel length is random and difficult to control.

[0004] It is worth mentioning that laser direct writing, as a powerful micromachining route, plays a key role in material synthesis and electronic device processing. For example, our group previously developed a laser burning method to trigger defect formation, thereby allowing single-crystalline m-TMD to selectively grow on s-TMD, thereby generating a series of m-TMD / s-TMD vdWH arrays. 4 . Park et al. 5 The rapid and selective preparation of MoS2 and WS2, as well as the patterned vertical heterostructure of MoS2 / WS2, were achieved on a wafer scale. Abbs et al.6 The selective synthesis of WS2 / MoS2 heterostructures was also achieved by laser printing technology. Compared with traditional photolithography, laser processing has outstanding advantages such as flexibility, high precision and no pollution. However, the simple and rapid preparation of imaged m-TMD / s-TMD heterostructures with controllable channel lengths still faces challenges.

[0005] References

[0006] 1C.Huang,S.Wu,AMSanchez,JJPeters,R.Beanland,JSRoss,P.Rivera,W.Yao,DHCobden,X.Xu,Nat.Mater.2014,13,1096.

[0007] 2. J. Shi, Y. Huan, X. Zhao, P. Yang, M. Hong, C. Xie, S. Pennycook, Y. Zhang, ACS Nano 2021, 15, 1858.

[0008] 3. Q. Ji, C. Li, J. Wang, J. Niu, Y. Gong, Z. Zhang, Q. Fang, Y. Zhang, J. Shi, L. Liao, X. Wu, L. Gu, Z. Liu, Y. Zhang, Nano Lett. 2017, 17, 4908.

[0009] 4Z.W.Zhang,Z.W.Huang,J.Li,D.Wang,Y.Lin,X.D.Yang,H.Liu,S.Liu,Y.L.Wang,B.Li,X.F.Duan,X.D.Duan,Nat.Nanotechnol.2022,17,493.

[0010] 5.S.Park,A.Lee,KHChoi,SKHyeong,S.Bae,JMHong,TWKim,BHHong,SKLee,ACS Nano 2020,14,8485.

[0011] 6.OAAbbas, AHLewis, N.Aspiotis, C.-C.Huang, I.Zeimpekis, DWHewak, P.Sazio, S.Mailis, Sci.Rep.2021,11,5211. Summary of the invention

[0012] In order to fill the gap in the preparation of patterned two-dimensional VX2 nanosheets, the first purpose of the present invention is to provide a method for preparing patterned two-dimensional VX2 materials, aiming to obtain clean, damage-free, and channel-length controllable patterned two-dimensional VX2 materials.

[0013] The second purpose of the present invention is to provide a patterned two-dimensional VX2 nanosheet obtained by the preparation method.

[0014] The third object of the present invention is to provide a method for preparing a patterned two-dimensional lateral or vertical VX2 / TMDs heterojunction.

[0015] A fourth object of the present invention is to provide a patterned two-dimensional heterojunction and a device.

[0016] Two-dimensional materials with different crystal structures can form lateral heterostructures or vertical van der Waals heterostructures (vdWHs), providing a rich material platform for exploring the transport of carriers and photons within atomic-scale interfaces. However, the fabrication of heterostructure devices relies on the cumbersome two-dimensional metal nanosheet transfer process, and the channel length is random and difficult to control. Laser direct writing, as a powerful micromachining approach, plays a key role in material synthesis and electronic device processing. Compared with traditional photolithography, laser processing has outstanding advantages such as flexibility, high precision and no pollution. However, the simple and rapid preparation of patterned m-TMD / s-TMD heterostructures with controllable channel lengths remains a challenge. In response to this problem, the present invention provides the following solutions:

[0017] A method for preparing a patterned two-dimensional VX2 material, comprising obtaining a two-dimensional VX2 material, then patterning and etching the material using a laser, and then treating the material with a hydrochloric acid solution to obtain the patterned two-dimensional VX2 material; wherein X is S or Se;

[0018] The power intensity of the laser is less than 3.5×10 5 W / cm 2 .

[0019] The present invention innovatively uses the laser of the power intensity to etch the two-dimensional VX2 material, and further combines it with hydrochloric acid treatment, so that the patterning of the two-dimensional VX2 material can be simply achieved, and a clean, lossless, and patterned two-dimensional VX2 material with controllable channel length can be produced.

[0020] In the present invention, the VX2 material can be obtained based on a known method. For example, as an illustrative scheme, the VX2 material is obtained by volatilizing VCl3 and X powder and performing CVD deposition in a carrier gas a.

[0021] The purity of VCl3 and X powder raw materials is greater than 99%.

[0022] In the present invention, the substrate for CVD deposition may be a conventional substrate, for example, a SiO2 / Si substrate with a thickness of 280 nm.

[0023] Preferably, the volatilization temperature of VCl3 is 550-650°C, and can further be 590-620°C.

[0024] Preferably, the X powder is S powder, and its volatilization temperature is 180-250° C. The X powder is Se powder, and its volatilization temperature is 380±20° C.

[0025] Preferably, the weight ratio of VCl3 to X powder is 1:2-5.

[0026] Preferably, the carrier gas a includes protective gas and hydrogen; preferably, the protective gas includes inert gas.

[0027] Preferably, in the carrier gas a, the flow rate of the protective gas is 50 to 100 sccm, and can be further 60 to 80 sccm, and the flow rate of the hydrogen gas is 1 to 5 sccm, and can be further 1 to 3 sccm.

[0028] In the present invention, the temperature of CVD deposition is 550-650°C, and can further be 590-620°C.

[0029] Preferably, the CVD deposition time is 5 to 15 minutes, and further can be 9 to 11 minutes.

[0030] In the present invention, the power intensity of the laser and the subsequent hydrochloric acid-alcohol treatment are the key to synergistically inducing clean and lossless patterning of two-dimensional VX2 materials.

[0031] Preferably, the power intensity of the laser is 1.0 to 3.5×10 5 W / cm 2 ; further can be 1.5~3.2×10 5 W / cm 2 ; further 1.7~1.9×10 5 W / cm 2 .

[0032] In the present invention, the laser spot size and the time the laser acts on the sample have little effect on the patterning behavior, so the length of the etched channel can be changed by changing the size of the laser spot, thereby achieving the purpose of controllable channel length.

[0033] In the present invention, the laser treatment time may be within 2 seconds, and further may be 0.01 to 2 seconds.

[0034] In the present invention, through the combined control of the laser and power, the physicochemical transformation of the laser irradiated part can be unexpectedly induced with high selectivity, and further combined with the subsequent solution hydrochloric acid treatment method, a highly crystalline and lossless pattern can be obtained.

[0035] Preferably, the solubility of the solute in the hydrochloric acid solution can be adjusted as needed. For example, considering the effect and efficiency, it can be 5M or more, further 10 to 12M, and further 11.6 to 12.0M.

[0036] Preferably, the temperature of the hydrochloric acid solution treatment stage is room temperature.

[0037] Preferably, the hydrochloric acid solution treatment time is 1 minute or more, further 1 to 10 minutes, and in consideration of treatment efficiency, may further be 2 to 4 minutes.

[0038] In the present invention, after the hydrochloric acid treatment, an alcohol solution treatment may be further performed. In the present invention, the alcohol treatment is used to accelerate the drying process.

[0039] Preferably, the alcohol solution is at least one of C1-C4 monoalcohols, diols and polyols.

[0040] The present invention also includes a patterned two-dimensional VX2 material obtained by the preparation method.

[0041] The present invention also provides a method for preparing a patterned two-dimensional lateral VX2 / TMDs heterojunction, wherein raw materials for synthesizing TMDs are deposited on the surface of a deposition substrate of the patterned two-dimensional VX2 material to obtain a patterned two-dimensional lateral VX2 / TMDs heterojunction.

[0042] The research of the present invention unexpectedly shows that the innovative use of the patterned two-dimensional lateral VX2 prepared by the method described in the present invention as a deposition substrate for TMDs can unexpectedly promote the lateral growth of TMDs along VX2, allowing TMDs to fill the pattern gaps and prepare a patterned two-dimensional lateral VX2 / TMDs heterojunction.

[0043] In the present invention, TMDs can be grown on the surface of a patterned two-dimensional lateral VX2 substrate based on conventional principles and methods.

[0044] For example, as an optional solution, the deposition method is CVD deposition;

[0045] For another example, the raw materials of the TMDs include a metal element source and a chalcogenide source, wherein the metal element source is at least one of an oxide and a chloride of the metal element; wherein the metal element includes at least one of W and Mo; and the chalcogenide source is at least one of sulfur and selenium.

[0046] An illustrative embodiment of the present invention, the TMDs is MoS2, and the synthesized patterned two-dimensional lateral VX2 / MoS2 heterojunction, wherein the metal element source can be MoO3. The oxygen group element source is sulfur. Wherein, the conditions for CVD deposition of MoS2 can be: the volatilization temperature of sulfur powder is 150-250°C, preferably 190-210°C. The volatilization temperature of MoO3 is 550°C-580°C and can further be 560±10°C; the carrier gas in the CVD stage is an inert gas, such as Ar. The flow rate of the carrier gas is 50-150sccm. The temperature in the CVD deposition stage is 550°C-580°C and can further be 560±10°C. Potassium chloride of 0.1-0.2% of its weight is also mixed into the raw material of MoO3. The time of CVD deposition is 5-15min. An optional solution is that when TMDs is WSe2, it can be obtained by conventional CVD and PVD methods. For example, when the PVD method is used, the volatilization temperature of WSe2 can be 1160±40°C; the carrier gas in the PVD stage can be an inert gas, and its flow rate can be 50-100 sccm; the PVD deposition time can be 1-10 min.

[0047] The present invention also provides a method for preparing a patterned two-dimensional vertical VX2 / TMDs heterojunction, wherein a TMDs two-dimensional material is prepared in advance, and VX2 is deposited on its surface to obtain a VX2 / TMDs heterojunction. Subsequently, the VX2 surface in the VX2 / TMDs heterojunction is subjected to laser patterning treatment, hydrochloric acid treatment, and alcohol treatment using the method described in the present invention to obtain the patterned vertical VX2 / TMDs heterojunction.

[0048] In the present invention, the VX2 / TMDs heterojunction can be grown based on known methods.

[0049] In the present invention, as an optional solution, the patterned two-dimensional vertical VX2 / TMDs heterojunction can be a patterned two-dimensional vertical VS2 / MoS2 heterojunction or a patterned two-dimensional vertical VSe2 / WSe2 heterojunction.

[0050] The present invention also provides a patterned two-dimensional heterojunction, which is the patterned two-dimensional lateral VX2 / TMDs heterojunction prepared by the present invention, or the patterned two-dimensional vertical VX2 / TMDs heterojunction.

[0051] The present invention also provides a device, which comprises the patterned two-dimensional heterojunction, or is prepared by the patterned two-dimensional heterojunction based on a known method.

[0052] For example, the optional steps for preparing the device of the present invention are:

[0053] The sample was exposed and marked on the patterned vertical VX2 / MoS2 metal / semiconductor heterostructure using electron beam exposure technology, and then metal was deposited on the sample using electron beam evaporation technology to prepare a field effect transistor.

[0054] The metal deposited by electron beam evaporation is Au.

[0055] Beneficial Effects

[0056] 1. The present invention shows that the combined control of the laser and power can control the physicochemical characteristics of the material in the laser area with high selectivity, and further cooperate with the treatment of hydrochloric acid to obtain a high crystallinity and lossless pattern. The patterned material obtained by the method can be used as a substrate to induce the lateral growth of other two-dimensional materials to obtain a lateral heterojunction. In addition, the patterning method of the present invention has good universality, and it can also pattern the performance of the heterojunction to obtain a patterned vertical heterojunction.

[0057] The present invention uses Raman, EDS and TEM characterizations to prove that the VX2 nanosheets after laser irradiation can be etched cleanly and have a clear interface after acid treatment, thereby providing a guarantee for the subsequent growth of heterogeneous structures.

[0058] 2. The present invention, thanks to the laser radiation etching method described in the present invention, provides the possibility for patterning of vertical VX2 / TMDs metal / semiconductor heterostructures. Thanks to the selective etching of VX2, the TMDs in the vertical heterostructure are not damaged, and a VX2-contacted TMDs transistor with a relatively short channel length (~400nm) is manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 Normal pressure chemical vapor deposition device for preparing VS2 two-dimensional materials;

[0060] Figure 2 This is a schematic diagram of the experimental process of Example 1-1, wherein the nanosheets are irradiated with laser, soaked in concentrated hydrochloric acid and then cleaned with ethanol, and a morphology and thickness diagram of the patterned VS2 nanosheets;

[0061] Figure 3 This is the EDS elemental analysis diagram of the patterned VS2 nanosheets of Example 1-1;

[0062] Figure 4 The laser power density used in Example 1-2 is 2.23×10 5 W / cm 2 Topography of VS2 after patterning;

[0063] Figure 5 The laser power density used in Example 1-2 is 3.11×10 5 W / cm2 Topography of VS2 after patterning;

[0064] Figure 6 This is a statistical graph showing the variation of sample thickness with laser power density in Example 1-2;

[0065] Figure 7 is the thickness of VS2 before and after etching using different laser power densities in Example 1-2. The blue area is less than 3.5×10 5 W / cm 2 , the red area is larger than 3.5×10 5 W / cm 2 ;

[0066] Figure 8 The EDS spectra of VS2 nanosheets after etching with different laser power densities in Example 1-2, where the blue curve uses a laser power density less than 3.5×10 5 W / cm 2 The red curve uses a laser power density greater than 3.5×10 5 W / cm 2 ;

[0067] Fig. 9 is the energy spectrum of the VS2 nanosheet gap under laser irradiation with different laser power densities in Example 1-2; Fig. 9 The laser power density used in AD is less than 3.5×10 5 W / cm 2 , Fig. 9 The laser power density used by EF is greater than 3.5×10 5 W / cm 2 ;

[0068] Fig.10 The morphology of the VS2 nanosheets after acid treatment under laser irradiation with different laser power densities in Example 1-2 is shown in FIG. Fig.10 b is the morphology of complete dissolution of VS2 nanogap under laser irradiation with low laser power density; Fig.10 c is the morphology of VS2 transformed into acid-insoluble nanoparticles under high laser power density laser irradiation;

[0069] Fig.11 The optical images and morphological images of the experimental group A treated with 5M hydrochloric acid in Examples 1-3;

[0070] Fig.12 The optical images of the samples of Experimental Group B fumigated with hydrochloric acid vapor at different times in Examples 1-3;

[0071] Fig.13For Examples 1-4, optical images and morphology thickness diagrams of VSe2 patterning under different laser power density irradiation; Fig.13 ad are the results under high power density radiation; Fig.13 eh is the result under low power density radiation;

[0072] Fig.14 This is an optical picture of the VS2 nanosheet after HF treatment and etching in Comparative Example 1-1;

[0073] Fig.15 Schematic diagram of the experimental device for synthesizing a lateral VS2-MoS2 metal / semiconductor heterostructure in Example 2-1 (15a), a structural schematic diagram of the synthesized lateral heterostructure (15b) and an optical picture (15c);

[0074] Fig.16 Raman characterization of the lateral VS2-MoS2 metal / semiconductor heterostructure synthesized in Example 2-1;

[0075] Fig.17 Optical image and Raman characterization of the vertical VS2 / MoS2 metal / semiconductor heterostructure synthesized in Example 2-2;

[0076] Fig.18 The morphology of MoS2 under different laser power density irradiation in Example 2-2;

[0077] Fig.19 Optical picture of the vertical VSe2 / WSe2 metal / semiconductor heterostructure synthesized in Example 2-3;

[0078] Fig. 20 Optical images and transfer characteristic curves of the lateral VS2-MoS2 metal / semiconductor heterostructure field effect transistor prepared in Example 3-1.

[0079] Fig.21 Optical images (small picture), output characteristic curves and transfer characteristic curves of the vertical VS2 / MoS2 metal / semiconductor heterostructure field effect transistor prepared in Example 3-2.

[0080] Fig. 22 Optical images (small picture), output characteristic curves and transfer characteristic curves of the vertical VSe2 / WSe2 metal / semiconductor heterostructure field effect transistor prepared in Example 3-3. DETAILED DESCRIPTION

[0081] The present invention is further described below through implementation cases, but the content of the present invention is not limited to the following content.

[0082] An optional scheme (Scheme A) of the present invention provides a two-dimensional VX2 nanosheet that can be prepared based on a known method, for example, an optional method, wherein the synthesis conditions of the two-dimensional VX2 nanosheet are:

[0083] 1T phase VX2 is grown at normal pressure on 280nm SiO2 / Si substrate, using VCl3 (AlfaAssar, ≥99%) and sulfur (AlfaAssar, ≥99.5%) as sources. The X source (such as sulfur source or selenium source) is placed in magnetic boat A and arranged upstream of the carrier gas; VCl3 and substrate are placed in magnetic boat B and arranged downstream of the carrier gas, and the temperature of the X source (temperature of magnetic boat A) and the temperature of the substrate (temperature of magnetic boat B) are controlled at T1 (when the X source is sulfur, its temperature is 200±20℃; when the X source is selenium, its temperature is 380±20℃) and 605±20℃ respectively, and deposited for 5~15min under the mixed flow of hydrogen (1~5sccm) and argon (50~100sccm), and then naturally cooled to ~300℃, and then the furnace is opened for rapid cooling.

[0084] In the present invention, the VX2 two-dimensional material obtained by the conventional method can be subjected to patterned etching by laser, and then treated with a hydrochloric acid solution to obtain a patterned two-dimensional VX2 material; the power intensity of the laser is less than 3.5×10 5 W / cm 2 .

[0085] The present invention provides an optional lateral heterojunction scheme (Scheme B), which uses the prepared patterned two-dimensional VX2 nanosheet as the deposition substrate of TMDs. The present invention takes MoS2 as TMDs and VS2 nanosheet as the patterned two-dimensional VX2 nanosheet. An optional patterned lateral VS2 / MoS2 metal / semiconductor heterostructure has the following preparation steps: a magnetic boat C containing sulfur powder is placed upstream of a deposition furnace of a single heating device, molybdenum oxide powder (5 mg 99.99% Alfa) is mixed with a trace amount of potassium chloride (0.1-0.2% of the weight of molybdenum oxide), placed in the middle of a porcelain boat D, and placed downstream of the deposition furnace. A 280nm SiO2 / Si substrate with patterned two-dimensional VS2 nanosheets is placed face down in the middle of a porcelain boat D containing molybdenum oxide powder. The temperature of magnetic boat C is controlled at 200±20°C, and the temperature of magnetic boat D is controlled at 560±20°C. Deposition is performed for 10 to 20 minutes under an inert atmosphere of carrier gas (flow rate is 100±50sccm), and then the mixture is cooled naturally.

[0086] The present invention provides an optional vertical heterojunction scheme (Scheme C), patterning two-dimensional VX2 nanosheets to synthesize a vertical VX2 / MoS2 metal / semiconductor heterostructure, the steps of which are to adopt the above-mentioned MoS2 process (Scheme B) to deposit MoS2 on a substrate (which can be a 280nm SiO2 / Si substrate), then adopt the above-mentioned VX2 deposition process of Scheme A to deposit VX2 on MoS2 to obtain a VX2 / MoS2 heterojunction, and then based on the patterning scheme of Scheme A, obtain the patterned vertical VX2 / MoS2 metal / semiconductor heterostructure.

[0087] The present invention provides an optional vertical heterojunction scheme (Scheme C), patterning two-dimensional VX2 nanosheets to synthesize vertical VX2 / TMD metal / semiconductor heterostructures. Scheme C1 is a patterned two-dimensional VS2 nanosheet to synthesize a vertical VS2 / MoS2 metal / semiconductor heterostructure, the steps of which are to use the above-mentioned MoS2 process (Scheme B) to deposit MoS2 on a substrate (which can be a 280nm SiO2 / Si substrate), then use the above-mentioned VX2 deposition process of Scheme A to deposit VS2 on MoS2 to obtain a VS2 / MoS2 heterojunction, and then based on the patterning scheme of Scheme A, obtain the patterned vertical VS2 / MoS2 metal / semiconductor heterostructure. Scheme C2 is to synthesize a vertical VSe2 / WSe2 metal / semiconductor heterostructure by patterning two-dimensional VSe2 nanosheets. The steps are: adopt an optional scheme. When TMDs is WSe2, it can be obtained by conventional CVD and PVD methods. For example, when the PVD method is adopted, the volatilization temperature of WSe2 can be 1160±40℃; the carrier gas in the PVD stage can be an inert gas, and its flow rate can be 50-100sccm; the PVD deposition time can be 1-10min. Then, the VX2 deposition process of the above-mentioned scheme A is adopted to deposit VSe2 on WSe2 to obtain a VSe2 / WSe2 heterojunction, and then based on the patterning scheme of scheme A, the patterned vertical VSe2 / WSe2 metal / semiconductor heterostructure is obtained.

[0088] In one embodiment of the present invention, the vertical VX2 / TMD metal / semiconductor heterostructure has a TMD greater than 50um, and more preferably greater than 100um.

[0089] In the present invention, the deposition process can be implemented with existing equipment, and only needs to meet the temperature control method.

[0090] In the present invention, the material of the present invention can be prepared into a device based on a known method.

[0091] 1. Preparation method of patterned VX2 (X=S, Se) two-dimensional materials

[0092] Example 1-1

[0093] Step (1):

[0094] The experimental setup for synthesizing VS2 two-dimensional materials is shown in Figure 2. Figure 1 As shown, S powder is placed in magnetic boat A upstream of the carrier gas, VCl3 (the weight ratio of sulfur powder and VCl3 is 5:1) is arranged in magnetic boat B downstream of the carrier gas, and the substrate (SiO2 / Si substrate) is placed flat on magnetic boat B with its deposition surface facing upward; carrier gas (hydrogen flow rate is 2sccm, Ar flow rate is 70sccm) is introduced into the deposition tube, and the temperature of magnetic boat A and magnetic boat B is controlled to make the temperature of magnetic boat A zone 200°C and the temperature of magnetic boat B zone 605°C. At this temperature and carrier gas, the deposition is carried out for 10 minutes to obtain VS2 two-dimensional material.

[0095] Step (2):

[0096] The VS2 two-dimensional material obtained in step (1) was subjected to patterning treatment, the steps being: using a 488 nm wavelength laser (with an intensity of 1.88×10 5 W / cm 2 ) The VS2 two-dimensional material was laser treated for 0.01 s, then placed in a 12 M hydrochloric acid solution, soaked for 2 min, treated with ethanol, and dried to obtain a patterned VS2 two-dimensional material.

[0097] Figure 2 a is the experimental flow chart of patterning treatment and acid-alcohol solution post-treatment of VS2. Figure 2 b and Figure 2 c are schematic diagrams of the material structure after laser etching and hydrochloric acid solution treatment. Figure 2 de is the optical image of VS2 after laser etching and its AFM morphology thickness map. Figure 2 fg are the optical images and AFM morphology thickness maps of the samples obtained after being immersed in 12M hydrochloric acid for 2 min and washed with ethanol.

[0098] Figure 3 This is the TEM characterization image of the patterned VS2 two-dimensional material obtained after acid treatment and ethanol cleaning; it shows that the prepared material has good crystallinity and component uniformity; the laser etched part has been completely cleaned by hydrochloric acid and ethanol treatment, and no V and S elements are found, proving that the two processes of laser etching and solution treatment can obtain a patterned structure of two-dimensional materials with a clean interface.

[0099] Example 1-2

[0100] Compared with Example 1-1, the only difference is that the laser power density is changed. The experimental groups are:

[0101] Group A: laser density is 2.23×10 5 ;

[0102] Group B: laser density was 3.11×10 5 ;

[0103] Comparative group A: laser power density is 4.23×10 5 W / cm 2 .

[0104] Other operations and parameters are the same as those in Example 1-1.

[0105] Figure 4 a The blue area is the experimental group A with a power density of 2.23×10 5 After laser etching, the sample was soaked in 12M concentrated hydrochloric acid for 2 minutes and then washed with ethanol. Figure 4 b The material morphology image confirms that a two-dimensional material patterned structure with a clean interface is obtained.

[0106] Figure 5 a The blue area is the experimental group B with a power density of 3.11×10 5 After laser etching, the sample was soaked in 12M concentrated hydrochloric acid for 2 minutes and then washed with ethanol. Figure 5 b The material morphology image confirms that a two-dimensional material patterned structure with a clean interface is obtained.

[0107] Figure 6 The statistical variation of VS2 nanosheet thickness under different confocal laser power densities is shown. When the power intensity is about 3.5×10 5 W / cm 2 When the power intensity is lower than the laser power threshold, the thickness of the irradiated area decreases, and vice versa, the thickness of the irradiated area increases.

[0108] Figure 7 This is an optical picture of the material after laser etching of Example 1-1 and Example 1-2, wherein: Figure 7 b is the low power density (1.88×10 5 W / cm 2 ) The laser irradiated area (blue frame area) produces a certain thinning effect, and the thickness of the laser irradiated area is 1.2nm thinner than the original thickness (7.5nm). Figure 7 The power of laser etching in the red frame area in a is the power of comparison group A in Example 1-2, Figure 7 a and Figure 7 bComparison shows that the higher power density (4.23×10 5 W / cm 2) resulted in a 2.3 nm increase in thickness, and a large number of aggregated nanoparticles could be found in the irradiated area. Once the laser power threshold (3.5×10 5 W / cm 2 ), the complete oxidation reaction of VS2 nanosheets leads to amorphous vanadium oxide (VO z )Particle formation.

[0109] Figure 8 Transmission electron microscopy was used to analyze the chemical composition of the products after laser irradiation with different power densities. 5 W / cm 2 ) under the condition that the photothermal oxidation process of VS2 is not sufficient, and only part of oxygen is doped to generate a ternary compound composed of V, S, and O (VS x O y )( Figure 8 The blue line in the figure is the test result of the laser-treated material of Example 1-1. Once the laser power threshold (3.5×10 5 W / cm 2 ), the complete oxidation reaction of VS2 nanosheets leads to amorphous vanadium oxide (VO z )Particle formation ( Figure 8 The red line in the figure is the test result of the laser-treated material of comparison group A in Example 1-2).

[0110] Fig. 9 ad is the low power density (1.88×10 5 W / cm 2 ) EDS analysis of the laser irradiation product, the distribution of the three elements V, O, and S can be clearly seen; Fig. 9 eh is higher than 3.5×10 5 W / cm 2 In the EDS analysis of the product after laser irradiation, only V and O elements are visible in the etched area, which further confirms the effect of laser power on VS2 nanosheets.

[0111] Fig.10 a is Figure 5 The samples were immersed in 12M concentrated hydrochloric acid for 2 minutes and then washed with ethanol to obtain the AFM morphology thickness map of the product. The results showed that the low power density (1.88×10 5 W / cm 2 ) The laser irradiation product can be dissolved in acid to form a clean interface; while the comparative group A in Example 1-2 is higher than 3.5×10 5 W / cm 2 After laser irradiation, the product is insoluble in acid and cannot be used for the next step of heterojunction synthesis.

[0112] Examples 1-3

[0113] Compared with Example 1-1, the only difference is that the concentration of hydrochloric acid is changed. The experimental groups are:

[0114] Group A: The concentration of hydrochloric acid was 5M;

[0115] Comparison with Group A: The laser-etched VS2 nanosheets were placed upside down on a 12M hydrochloric acid solution (not in contact with hydrochloric acid), and VS2 was fumigated with HCl vapor at 60°C. The actual hydrochloric acid concentration acting on VS2 was higher than 12M:

[0116] Group A: hydrochloric acid concentration was 5 M, treatment time was 5 min, power density was 1.88×10 5 W / cm 2 After laser etching the VS2 nanosheet, the etched part was removed cleanly after soaking in 5M hydrochloric acid for 5 minutes. Fig.11 a shows the optical image of VS2 after etching. Fig.11 b shows the optical image of VS2 after immersion in 5M hydrochloric acid for 5 minutes. Fig.11 c is the AFM morphology image.

[0117] Compared with Group A: The hydrochloric acid concentration is HCl vapor, and the actual hydrochloric acid concentration acting on VS2 is higher than 12M. Fig.12 a is the original optical image of VS2, Fig.12 b is the optical picture of VS2 smoked for 30 seconds. Fig.12 c is the optical image of VS2 after fumigation for 5 minutes. After this method, the etched channel has material adsorption, which is not conducive to the subsequent heterojunction synthesis.

[0118] By comparison with Example 1-1, it can be seen that by using the hydrochloric acid solution method and setting the hydrochloric acid concentration to above 10 M, better lossless patterning and crystallinity can be obtained.

[0119] Examples 1-4

[0120] Example 1-1 is the preparation of patterned two-dimensional material VS2, and Example 1-4 is the preparation of patterned two-dimensional material VSe2, wherein the preparation method is the same as that of Example 1-1, except that the sulfur powder is replaced with selenium powder, and the volatilization temperature of the area where the selenium powder is located (the temperature of the magnetic boat A is controlled in the area of ​​380±5°C); in addition, the patterning treatment method and conditions of step 2 of Example 1-1 are used to carry out patterning treatment, and other operations and parameters are the same as those of Example 1-1.

[0121] (1.88×10 5 W / cm 2 ) Laser irradiated VSe2 nanosheets ( Fig.13e, f) After being immersed in 12M concentrated hydrochloric acid solution for 2 min and cleaned with ethanol, the AFM morphology thickness images are shown in Figure 2. Fig.13 As shown in h, the etched part has been completely etched, forming a relatively clean interface. Similar to the control group A of Example 1-2, the power density used in the control group A of Example 1-2 is 4.23×10 5 W / cm 2 When high-power laser irradiates VSe2, the thickness of the irradiated area increases and it is insoluble in acid ( Fig.13 ad).

[0122] Comparative Example 1-1

[0123] Compared with Example 1-1, the only difference is that HF ​​is used to replace the HCl, and other operations and parameters are the same as Example 1-1.

[0124] Fig.14 a is an optical picture of VS2 after etching in Example 1-1, Fig.14 b is the optical picture of VS2 after being immersed in HF solution for 1 minute. It can be seen that the surface of VS2 nanosheets has been damaged after being treated with HF solution, which is not conducive to subsequent growth.

[0125] 2. Method for preparing patterned two-dimensional lateral and vertical VX2 / MX2 (X=S, Se, M=Mo, W) metal / semiconductor heterostructures

[0126] Example 2-1 - Preparation of patterned lateral VS2 / MoS2 heterojunction

[0127] The preparation steps are as follows: a magnetic boat C containing sulfur powder is placed upstream of a deposition furnace of a single heating device, molybdenum oxide powder (5 mg 99.99% Alfa) is mixed with a trace amount of potassium chloride (0.1-0.5% of the weight of molybdenum oxide), placed in the middle of a porcelain boat D, and placed downstream of the deposition furnace. A 280nm SiO2 / Si substrate with patterned two-dimensional VS2 nanosheets (prepared in Example 1-1) is placed face down in the middle of a porcelain boat D containing molybdenum oxide powder. The temperature of the magnetic boat C is controlled to be 200°C, and the temperature of the magnetic boat D is controlled to be 560°C, and the deposition is carried out for 15 minutes under an inert atmosphere of a carrier gas (flow rate of 100 sccm), and then cooled naturally to obtain the product. Fig.15 a is a schematic diagram of the experimental device for growing lateral VS2 / MoS2 metal / semiconductor heterostructures. When the pre-patterned VS2 is used as a growth template for subsequent epitaxial growth, MoS2 tends to nucleate at the edge and gradually fill the nanogaps of VS2, which is thermodynamically favorable due to the abundant dangling bonds at the edge. Therefore, a patterned VS2-MoS2 lateral heterostructure was prepared, in which the pink area is MoS2 and the blue area is VS2 ( Fig.15 c).

[0128] Fig.16 The Raman spectroscopy characterization in a further confirms the successful formation of the lateral heterostructure. The Raman characteristic peaks of VS2 (red line) and MoS2 (green line and blue line) can be detected in the heterostructure. -1 、165cm -1 and 300cm -1 The Raman peak belongs to 1T-VS2, and the peak at 384 cm -1 and 404cm -1 The characteristic peaks are consistent with those of MoS2. Raman mapping studies further confirmed the formation of VS2 / MoS2 lateral heterojunction ( Fig.16 b,c).

[0129] Example 2-2-Patterned vertical VS2 / MoS2 heterostructure

[0130] Compared with Example 2-1, the only difference is that Example 2-2 uses MoS2 as a growth template to grow VS2 nanosheets, and then performs patterned etching on the VS2 nanosheets to prepare a patterned two-dimensional vertical VS2 / MoS2 heterostructure. The specific operation is referred to Example 1-1. The steps include:

[0131] Step (a): MoS2 nanosheet preparation

[0132] The synthesis method and conditions of MoS2 refer to the conditions of Example 2-1, for example, the magnetic boat C containing sulfur powder is set upstream of the deposition furnace of the single heating device, molybdenum oxide powder (5mg 99.99% Alfa) is mixed with a trace amount of potassium chloride (0.1-0.5% of the weight of molybdenum oxide), placed in the middle of the porcelain boat D, and set downstream of the deposition furnace. The 280nm SiO2 / Si substrate is placed face down in the middle of the porcelain boat D containing molybdenum oxide powder. The temperature of the magnetic boat C is controlled to 200°C, the temperature of the magnetic boat D is controlled to 560°C, and the deposition is carried out for 15 minutes under the carrier gas of the inert atmosphere (flow rate is 100sccm), and then naturally cooled to grow MoS2 nanosheets on the substrate.

[0133] Step (b): VS2 / MoS2 heterostructure preparation

[0134] The method of growing VS2 nanosheets on MoS2 nanosheets can refer to the preparation of VS2 nanosheets in Example 1, and the steps are, for example:

[0135] S powder is placed in magnetic boat A upstream of the carrier gas, VCl3 is set in magnetic boat B downstream of the carrier gas, and the substrate (MoS2 nanosheet SiO2 / Si substrate grown in step a) is placed flat on magnetic boat B; carrier gas (hydrogen flow rate is 2sccm, Ar flow rate is 70sccm) is introduced into the deposition tube, and the temperature of magnetic boat A and magnetic boat B is controlled to make the temperature of magnetic boat A zone 200°C and the temperature of magnetic boat B zone 605°C. At this temperature and carrier gas, the deposition is carried out for 10 minutes to obtain VS2 / MoS2 heterostructure.

[0136] Step (c): Patterning

[0137] The VS2 on the surface of the VS2 / MoS2 heterostructure was patterned and treated with hydrochloric acid using the conditions of Example 1-1, the steps being:

[0138] The VS2 / MoS2 heterostructure prepared in step (2) was patterned by using a 488 nm laser (with an intensity of 1.88×10 5 W / cm 2 ) The VS2 / MoS2 heterostructure was laser treated for 0.1s, then placed in a 12M hydrochloric acid solution, soaked for 2min, treated with ethanol, and dried to obtain a patterned VS2 / MoS2 heterostructure.

[0139] Fig.17 The vertical vdW VS2 / MoS2 heterostructure is patterned. When the growth order of VS2 and MoS2 is changed, that is, MoS2 is used as a template for the epitaxial growth of VS2, a vertical vdW VS2 / MoS2 heterostructure can be grown. The method is the same as that in Example 1-1, and the power intensity is less than 3.5×10 5 W / cm 2 Laser etching of vertical vdW VS2 / MoS2 heterostructures. From the optical image ( Fig.17 a) It can be seen that etching only occurs in the upper layer VS2, resulting in a patterned vertical vdW VS2 / MoS2 heterostructure. Fig.17 bc Raman characterization confirms the formation of patterned vertical vdW VS2 / MoS2 heterojunction. Raman mapping shows that there is no Raman peak of VS2 in the channel region, while the Raman peak of MoS2 is consistent with the original surface, which provides strong evidence for the selective etching of VS2 without damaging the underlying MoS2.

[0140] Fig.18 The morphology of MoS2 etched with different laser powers. The laser power intensities of lines 1 to 6 are 1.88×10 5 W / cm 2 , 9.92×10 4W / cm 2 ,1.40×0 5 W / cm 2 ,4.23×0 5 W / cm 2 ,4.23×0 5 W / cm 2 ,2.23×0 5 W / cm 2 From the AFM images, it can be seen that the laser power threshold for pure MoS2 oxidation is slightly lower than that for VS2 radiation, ensuring that MoS2 oxidation does not occur during post-treatment.

[0141] Example 2-3 Patterned vertical VSe2 / WSe2 heterojunction

[0142] Compared with Example 2-2, the only difference is that step (a) grows WSe2, wherein the preparation steps of WSe2 are: weigh 100 mg of WSe2 powder and place it in a quartz boat, place it in the center of the temperature zone of the tube furnace, and place the SiO2 / Si substrate in the downstream transition temperature zone. Purge the reaction chamber with 1000 sccm of high-purity argon for 10 minutes to remove residual oxygen and moisture in the chamber. Then, under 80 sccm of argon, raise the temperature of the central temperature zone to 1160°C with a reverse gas flow (gas flows from the substrate to the raw material), and then switch the gas flow to a constant temperature of 5 minutes with a forward gas flow. Cool naturally to obtain a WSe2 substrate.

[0143] In step b, VSe2 nanosheets are grown, that is, the sulfur powder in step b is replaced with selenium powder, and the temperature of the area where the selenium powder is located is 380±5°C; a VSe2 / WSe2 heterojunction is obtained;

[0144] In step c, VSe2 is patterned using the method of Examples 1-3.

[0145] Other operations and parameters are the same as those in Example 2-2.

[0146] The VSe2 nanosheets were then patterned and etched to prepare a patterned two-dimensional vertical VSe2 / WSe2 heterostructure ( Fig.19 ).

[0147] 3. Fabrication of patterned vertical VS2 / MoS2 metal / semiconductor heterostructure field effect transistors

[0148] The preparation steps of field effect tube are as follows:

[0149] The electron beam exposure technology is used to blast the required electrodes on the metal material on the patterned heterostructures of Example 2-1, Example 2-2, and Example 2-3, and then 60nm Au is deposited by electron beam evaporation, and the excess metal is stripped off to obtain a vertical VS2 / MoS2 metal / semiconductor heterostructure field effect transistor.

[0150] Example 3-1

[0151] Fig. 20 Optical images and transfer characteristic curves of the patterned lateral VS2 / MoS2 metal / semiconductor heterostructure field effect transistor synthesized in Example 2-1.

[0152] Example 3-2

[0153] Fig.21 The output characteristic curve and transfer characteristic curve of the patterned vertical VS2 / MoS2 metal / semiconductor heterostructure field effect transistor synthesized in Example 2-2. Based on the patterned VS2 / MoS2 vdW heterostructure, a VS2 contact MoS2 transistor with a relatively short channel length (~400nm) can be easily manufactured, such as Fig.17 As shown in panel a, the obtained single-layer MoS2 transistor with vdW contacts shows a linear I ds -V ds The on-state current of the device is 4.01 μA μm -1 , the on / off ratio is ~2.89×10 6 , the field effect mobility is ~3.56cm 2 s -1 V -1 .

[0154] Example 3-3

[0155] Fig. 22 The output characteristic curve and transfer characteristic curve of the patterned vertical VSe2 / WSe2 metal / semiconductor heterostructure field effect transistor synthesized in Example 2-3. The VSe2 contact device shows a satisfactory near-linear relationship, and the generated on-current is 10μAμm -1 ( Fig.18 a). The transfer characteristics of the corresponding WSe2 transistor show typical p-type transistor behavior with an on / off current ratio close to 5×10 5 .

Claims

1. A method for preparing a patterned two-dimensional VX2 material, characterized in that: A two-dimensional VX2 material is obtained, and then patterned etching is performed on it by laser, and then treated with a hydrochloric acid solution to obtain a patterned two-dimensional VX2 material; wherein X is S or Se; The power intensity of the laser is less than 3.5×10 5 W / cm 2 .

2. The method for preparing the patterned two-dimensional VX2 material according to claim 1, characterized in that: The VX2 material is obtained by volatilizing VCl3 and X powder and performing CVD deposition in carrier gas a; Preferably, the volatilization temperature of VCl3 is 550-650°C; Preferably, the X powder is S powder, and its volatilization temperature is 180-250°C; the X powder is Se powder, and its volatilization temperature is 380±20°C; Preferably, the weight ratio of VCl3 to X powder is 1:2-5; Preferably, the carrier gas a comprises a protective gas and hydrogen; preferably, the protective gas comprises an inert gas; Preferably, in the carrier gas a, the flow rate of the protective gas is 50 to 100 sccm, and the flow rate of the hydrogen gas is 1 to 5 sccm; Preferably, the CVD deposition time is 5 to 15 minutes.

3. The method for preparing the patterned two-dimensional VX2 material according to claim 1, characterized in that: The power intensity of the laser is 1.0 to 3.5×10 5 W / cm 2 .

4. The method for preparing the patterned two-dimensional VX2 material according to claim 1, characterized in that: The solute solubility in the hydrochloric acid solution is 5M or more, further 10 to 12M, further 11.6 to 12.0M; Preferably, the temperature of the hydrochloric acid solution treatment stage is room temperature; Preferably, the hydrochloric acid solution treatment time is more than 1 minute, and can further be 1 to 10 minutes; Preferably, after the hydrochloric acid treatment, an alcohol solution treatment may be further performed; Preferably, the alcohol solution is at least one of C1-C4 monoalcohols, diols and polyols.

5. A patterned two-dimensional VX2 material obtained by the preparation method according to any one of claims 1 to 4.

6. A method for preparing a patterned two-dimensional lateral VX2 / TMDs heterojunction, characterized in that: The raw materials for synthesizing TMDs are deposited on the surface of the deposition substrate of the patterned two-dimensional VX2 material as described in claim 5 to obtain a patterned two-dimensional lateral VX2 / TMDs heterojunction.

7. The method for preparing a patterned two-dimensional lateral VX2 / TMDs heterojunction according to claim 6, characterized in that: The deposition method is CVD deposition; Preferably, the raw materials of the TMDs include a metal element source and a chalcogenide source, wherein the metal element source is at least one of an oxide and a chloride of the metal element; wherein the metal element includes at least one of W and Mo; and the chalcogenide source is at least one of sulfur and selenium.

8. A method for preparing a patterned two-dimensional vertical VX2 / TMDs heterojunction, characterized in that: A TMDs two-dimensional material is prepared in advance, and VX2 is deposited on its surface to obtain a vertical VX2 / TMDs heterojunction. Subsequently, the VX2 surface in the VX2 / TMDs heterojunction is subjected to laser patterning, hydrochloric acid treatment and alcohol treatment using the method described in any one of claims 1 to 4 to obtain the patterned vertical VX2 / TMDs heterojunction.

9. A patterned two-dimensional heterojunction, characterized in that: It is a patterned two-dimensional lateral VX2 / TMDs heterojunction prepared by the method of any one of claims 6 to 7, or a patterned two-dimensional vertical VX2 / TMDs heterojunction prepared by the preparation method of claim 8.

10. A device, characterized in that: Comprising the patterned two-dimensional heterojunction described in claim 9, or prepared by the patterned two-dimensional heterojunction; Preferably, the device is a field effect transistor device.

Citation Information

Patent Citations

  • Preparation method and application of MoS2@VS2@NiCo2O4 ternary photocatalyst

    CN110841659A

  • Synthesis and application of two-dimensional metal-semiconductor Van der Waals heterojunction array

    CN111146079A

  • Vertical monomolecular film field effect transistor based on two-dimensional laminated heterostructure and preparation method of vertical monomolecular film field effect transistor

    CN112582541A

  • Monomolecular field effect transistor based on two-dimensional Van der Waals heterostructure and preparation method of monomolecular field effect transistor

    CN112582542A

  • Preparation method of two-dimensional molybdenum-tungsten-sulfur vertical heterostructure

    CN112663021A